The effects of multicultural family support services on the longitudinal changes of acculturative stress, peer relations, and school adjustment - Ahn, Hyun Seon; Lee, Jeesoo; Jin, Yuanying (Frontiers in Psychology, 2024)
This study investigated the long-term trends of acculturative stress, peer relationship, and school adjustment among adolescents from multicultural families in South Korea, and examined the concurrent and lagged effects of multicultural family support services (MFSS) on the longitudinal changes in the variables of interest. Concurrent and lagged models as well as developmental trajectories via latent growth modeling (LGM) were employed on a sample of 1443 middle school students (706 boys, 737 girls) from the Multicultural Youth Panel Survey (MAPS). The results revealed that peer relationships and school adjustment perceived by adolescents demonstrated consistent, gradual declines across three-year time points while there was a lack of significant change in acculturative stress during the same period. The absence of significant change in acculturative stress could be attributed to floor effects, stemming from its initial low mean level. Nevertheless, the LGM modeling also exhibited significant concurrent and lagged effects of MFSS at the first and third time points of investigation. The intermittent significant effects of MFSS and the direction of its improvement were discussed. More educational interventions guiding students from multicultural families would be needed as they navigate the complexities of adolescence.